2021
DOI: 10.1101/2021.06.06.21253270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the role of polygenic background on the penetrance of monogenic forms in Parkinson’s disease

Abstract: Background: Several rare and common variants are associated with Parkinson's disease. However, there is still an incomplete penetrance in the carriers of rare variants associated with Parkinson's disease. To address this issue, we investigated whether a PRS calculated from significant GWAS SNPs affects the penetrance of Parkinson's disease among carriers of rare monogenic variants in known Parkinson's disease genes and those with a family history. Methods: We calculated the PRS based on common variants and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…An overlapping genetic basis between complex traits and monogenic conditions is becoming increasingly apparent across the genome. Deleterious variants in genes causative of monogenic disease can be further dysregulated by non-coding variants that are associated with common traits, and monogenic forms of numerous common complex diseases have been identified ( Peltonen et al, 2006 ; Chami et al, 2020 ; Hassanin et al, 2021 ). This overlap can cause considerable complexity when it comes to determining genotype–phenotype relationships ( Freund et al, 2018 ).…”
Section: Challenges Within Determining Penetrance and Expressivitymentioning
confidence: 99%
“…An overlapping genetic basis between complex traits and monogenic conditions is becoming increasingly apparent across the genome. Deleterious variants in genes causative of monogenic disease can be further dysregulated by non-coding variants that are associated with common traits, and monogenic forms of numerous common complex diseases have been identified ( Peltonen et al, 2006 ; Chami et al, 2020 ; Hassanin et al, 2021 ). This overlap can cause considerable complexity when it comes to determining genotype–phenotype relationships ( Freund et al, 2018 ).…”
Section: Challenges Within Determining Penetrance and Expressivitymentioning
confidence: 99%
“…We used the available imputed genotype array data through the UKB (Bycroft et al, 2018). We excluded outliers with high genotype missing rates, putative sex chromosome aneuploidy, and discordant reported sex vs. genotypic sex (Hassanin et al, 2021). We randomly excluded one from each pair of related individuals if the genetic relationship was closer than the second degree, defined as kinship coefficient >0.0884 as calculated by the UKB.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Hence, predictive machine learning models are needed, which can potentially also overcome one of the typical limitations of PRS, namely lacking variant interactions and thus non-linearities. A recent study shows the combined role of PRS, rare high-impact variants, and family history in PD risk ( Hassanin et al, 2021 ). Cope et al demonstrated that a non-linear machine learning algorithm purely trained on genetic variants can result in dramatically improved prediction performances compared to a classical PRS ( Cope et al, 2021 ).…”
Section: The Perspective Of Machine Learningmentioning
confidence: 99%